2018
DOI: 10.1038/s41598-018-20301-8
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IL-23 and IL-5 as surrogate markers of lesion metabolic activity in patients with hepatic alveolar echinococcosis

Abstract: Fluorodeoxyglucose (FDG) uptake by alveolar echinococcosis (AE) liver lesions is a signal of their metabolic activity and of disease progression. In order to find a surrogate marker for this status, we investigated whether parameters of the peripheral and/or periparasitic immune responses were associated with metabolic activity in a prospective case-control study of 30 AE patients and 22 healthy controls. Levels of 18 cytokines and chemokines, representative of innate and adaptive immune responses, were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(48 reference statements)
2
17
0
Order By: Relevance
“…The predominance of a T helper 2 (Th2) profile, including interleukin-5 (IL-5)-and IgE-dependent reactions, and high levels of IL-10 cytokine at the chronic stage of both AE and CE in humans have been known for some time (64). In CE, a dominant Th2/T regulatory (Treg) cytokine profile is rapidly established after the formation of the adventitial fibrous barrier (293,294). In AE, the immune response follows a 3-stage course characterized by a mixed Th1/Th2 profile at the early stage, a dominant Th2/Treg profile, including IL-10 and transforming growth factor ␤ (TGF-␤) regulatory cytokines, at the chronic middle stage, and a T-cell exhaustion status at the final stage of infection (289,295).…”
Section: Improving Understanding Of Immunological Mechanisms Of Host-mentioning
confidence: 99%
See 1 more Smart Citation
“…The predominance of a T helper 2 (Th2) profile, including interleukin-5 (IL-5)-and IgE-dependent reactions, and high levels of IL-10 cytokine at the chronic stage of both AE and CE in humans have been known for some time (64). In CE, a dominant Th2/T regulatory (Treg) cytokine profile is rapidly established after the formation of the adventitial fibrous barrier (293,294). In AE, the immune response follows a 3-stage course characterized by a mixed Th1/Th2 profile at the early stage, a dominant Th2/Treg profile, including IL-10 and transforming growth factor ␤ (TGF-␤) regulatory cytokines, at the chronic middle stage, and a T-cell exhaustion status at the final stage of infection (289,295).…”
Section: Improving Understanding Of Immunological Mechanisms Of Host-mentioning
confidence: 99%
“…Clinical studies on CE have shown the response to anti-infective therapy (or of "inactive" cyst) is associated with a Th1 profile, whereas on the other hand, resistance to treatment (or of "active" cyst) is associated with a Th2 profile and elevated IL-10 levels (289,293). Clinical studies in AE suggest that a combination of Th2-related cytokine serum levels, such as those of IL-23 and IL-5, could be used as a surrogate marker of AE metabolic activity in humans (294). Some proteins likely serve as messengers for cross talk between E. granulosus and its hosts and may also prove useful as targets for improved immunodiagnosis or patient follow-up (261,262).…”
Section: Improving Understanding Of Immunological Mechanisms Of Host-mentioning
confidence: 99%
“…Moreover, the LME region may directly affect the experimental outcome when not balanced properly by mimicking real experimental liver tissue with the real control liver tissues. A previous research has studied surrogate markers in distinguishing metabolically active and inactive AE patients [26]. In this study, methodology for sampling was de ned as "specimens were taken from the AE lesion area and from a macroscopically normal distant area of liver tissue", however, the precise area has not been described, but there was a well consideration for control liver tissue acquisition based on pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the LME region may directly affect the experimental outcome when not balanced properly by mimicking real experimental liver tissue with the real control liver tissues. A previous research has studied surrogate markers in distinguishing metabolically active and inactive AE patients [26]. In this study, methodology for sampling was defined as "specimens were taken from the AE lesion area and from a macroscopically normal distant area of liver tissue", however, the precise area has not been described, but there was a well consideration for control liver tissue acquisition based on pathology.…”
Section: Discussionmentioning
confidence: 99%